Efektivitas Slims dalam Bibliografi dan Pengolahan Bahan Pustaka di Perpustakaan Perguruan Tinggi (studi kasus Perpustakaan Universitas Negeri Surabaya) - Eka Rosanti, Febrin (PELITA JURNAL PENELITIAN DAN KARYA ILMIAH, 2025)
The development of information technology encourages academic libraries to implement automation systems in bibliographic activities and library material processing. This study aims to analyze the effectiveness of the Senayan Library Management System, or SLiMS, in bibliographic data entry and library material processing at the Universitas Negeri Surabaya Library. This study employed a quantitative descriptive approach using a survey method. Data were collected through questionnaires, structured interviews, and observations involving junior expert librarians, skilled librarians, and technical staff from faculty reading rooms. The results indicate that SLiMS supports librarians in bibliographic data entry, cataloging, classification, label printing, barcode creation, and information retrieval. However, the available features have not been utilized optimally. Some librarians still conduct classification, cataloging, and label printing manually. Other challenges include limited understanding of the latest SLiMS features, low awareness of professional development, and inadequate coordination between the university library and faculty reading rooms. These conditions lead to inconsistencies in bibliographic descriptions, delays in collection processing, and difficulties in information retrieval. This study concludes that SLiMS can effectively support bibliographic activities and library material processing when its features are fully utilized and supported by staff competency development and stronger collaboration among library personnel.